Assessment of renal function in hyperthyroid cats managed with a controlled iodine diet - Vaske, Heather (Kansas State University, 2015)
Hyperthyroidism is the most common endocrinopathy of geriatric cats and has physiologic effects on almost every organ in the body. It specifically affects the kidneys by increasing renal blood flow and glomerular filtration rate. In addition, activation of the renin angiotensin aldosterone system (RAAS) is increased and ultimately leads to efferent glomerular arteriole constriction and potentially glomerular hypertension. The classic treatment modalities for feline hyperthyroidism (anti-thyroid medication, radioiodine or surgery) have been evaluated for their overall effects on renal function. Studies have demonstrated that glomerular filtration rate (GFR) declines and serum creatinine increases with hyperthyroid treatment independent of the treatment modality. Hill’s® Prescription Diet® y/d® Feline, a relatively new dietary treatment modality for feline hyperthyroidism with controlled iodine concentrations, reduced phosphorus and protein, and increased omega-3 fatty acids, has been shown to significantly decrease thyroid hormone levels. The research provided in this report is the first evaluating the posttreatment effects of y/d® Feline on renal function. In agreement with previous studies, our research found that y/d® Feline resulted in a significant decrease in thyroid hormone levels. However, in contrast to other treatment modalities, y/d® Feline did not result in a significant decline in GFR, and it did result in a significant decline in mean serum creatinine concentration. These data indicate that y/d® Feline, as a treatment for feline hyperthyroidism, does not have a negative effect on renal function.
Keywords: Hyperthyroidism; Chronic kidney disease